Villy Sørensen’s Hermeneutics of the Fall - Petronytė, Rasa Alė (Literatūra, 2025)
The article interprets Danish modernist writer Villy Sørensen’s short story “The Soldier’s Christmas Eve”, published in Harmless Tales in 1955, on the basis of Paul Ricœur’s hermeneutics of symbols, which is concerned with the problem of the constitution of consciousness. Sørensen’s notion of the Fall is understood as a fragmentation of the original unity and a transition from coherence to a state defined by discordance. In this sense, the poetics of the Fall is read as a configuration of the Ricœurian two-way hermeneutics: the archaeology of consciousness that unmasks symbols and the eschatology that reflects on them in a renewed way. The interpretation of the short story “The Soldier’s Christmas Eve” highlights several aspects of the hermeneutics of symbols which constitute consciousness: (1) the unmasking of consciousness by revealing the split in the psyche is irreversible, (2) the archaeology and eschatology of the subject are interrelated: they contradict each other, yet are mutually constitutive, (3) the conscious becomes true consciousness only by adopting the hermeneutical task: consciousness is the act of interpreting representations of meaning outside the conscious. In this regard, the short story presents the Fall as a crucial element in the development of consciousness. By interpreting the Fall, the story itself becomes a hermeneutics of symbols.
Keywords: Villy Sørensen; the Fall; repetition; Paul Ricœur; hermeneutics of symbols